(untitled) (Research, Society and Development, 2021)
The development of new active ingredients in the context of Neglected Tropical Diseases (NTDs), remains a big challenge to the society. Among NTDs it is worth highlight the Chagas disease (CD) which has high morbidity and mortality. This study aims to retrieve information about the current scenario as well as new strategies and innovations in the pharmacological treatment of CD. For this purpose, a narrative review was conducted in which the articles were selected in PubMed, SciELO and LILACS, in the period between 2015/2020. Seeking to assess in order of relevance in academia the data were observed in results of publications in the SciELO between 1950/2019, about CD, diabetes mellitus and cancer. Information on clinical trials was also searched at ClinicalTrials.gov. In the last 20 years the number of publications on CD in SciELO was significantly lower compared to diabetes mellitus and cancer. Moreover, only two drugs are available, benznidazole and nifurtimox, which have limitations such as the amount of adverse effects. Therefore, new therapeutic options have been studied mainly in the case of benznidazole and have shown promising results by optimizing toxicity, absorption and bioavailability, for example. With regard to clinical trials, a total of seven studies were found, which investigate five compounds for the treatment of CD. Only one of the compounds has no clinical use yet, selenium, which suggests a deficiency in the search for new drug candidates. Such information reinforces, therefore, the neglected character of CD, as well as emphasizing the importance of researching new therapies.